Wear and corrosion behavior of vanadium-alloyed nodular cast irons fabricated by sand-casting - Turu, Irem Cemre; Gecu, Ridvan (ELSEVIER SCIENCE SA, 2023)
Nodular cast irons have been mainly used in automobile components exposed to large forces like brake pads, suffering from abrasion against recently developed lightweight Al2O3-containing brake rotors during operation. Besides, aqueous corrosion (rain, snow, and chlorides) can cause these brake pads to wear out faster. This study examined the wear and corrosion properties of the V-alloyed nodular cast irons as a function of V content (0, 0.25, 0.5, 0.75, and 1 wt%). The samples were tested against an Al2O3 ball to simulate more severe abrasive conditions, whereas the electrochemical corrosion behavior was investigated in a 3.5 wt% NaCl solution. It was revealed that wear resistance increased with increasing V up to 0.50 wt%, but higher V caused a reduction due to the heavily branched eutectic carbide formation. Wear losses increased with the applied load, whereas sliding speed had no significant effect. The samples experienced uniform and graphitic corrosion in a 3.5 wt% NaCl environment. Increasing V improved their corrosion resistance to 0.75 wt% V due to the precipitated spherical vanadium carbides. The 1 wt% V-alloyed sample failed both wear and corrosion tests because of increased metastable eutectic carbides.
Keywords: Nodular cast iron; Vanadium; Wear; Corrosion; Tafel extrapolation; DUCTILE IRON; MECHANICAL-PROPERTIES; FATIGUE BEHAVIOR; MICROSTRUCTURE; RESISTANCE; COATINGS; Engineering; Materials Science